Self-Repairing Carry-Lookahead Adder With Hot-Standby Topology Using Fault-Localization and Partial Reconfiguration - Muhammad Ali Akbar; Bo Wang; Amine Bermak (IEEE Open Journal of Circuits and Systems, 2022)
In this paper, a self-checking and -repairing carry-lookahead adder (CLA) is proposed with distributed fault detection ability. The presented design with self-checking and fault localization ability requires an area overhead of 69.6% as compared to the conventional CLA. It can handle multiple faults simultaneously without affecting the delay of conventional CLA, with the condition that each module has a single fault at a time. The repairing operation utilizes the hot-standby approach with partial reconfiguration in which the faulty module would be replaced by an accurately functioning module at run-time. The proposed self-repairing adder with high fault coverage requires 161.5% area overhead as compared to conventional CLA design which is 35.3% less as compared to the state-of-the-art partial self-repairing CLA. Moreover, the delay of the proposed 64-bit self-repairing CLA is 40.7% more efficient as compared to conventional ripple carry adder.